Power factor correction using boost converter technique: article / Nur Zati Akmar Lukeman - Lukeman, Nur Zati Akmar (2013)
This paper describes a single phase rectifier with improved power factor by using the boost converter technique. Low power factor is caused by non-linearity of the input current. Boost converter is one method of re-shaping the input waveform to be same pattern with the sinusoidal input voltage. The boost converter acts as a Power Factor Correction (PFC) of the input circuit. The complete design has developed and tested by using PSI.M simulation software. The results were compared without PFC and passive PFC and active PFC. Finally the simulation results are shown to verify the performance of this modified PFC. Significant percentage of reiiuction for the III!) and percentage of improvement for power factor is achieved by active PFC.